Disoriented disciplines : China, Latin America, and the shape of world literature - Hubert, Rosario (Northwestern University Press, 2024)
"This is a study of the archival formations, theoretical debates, and geopolitical frameworks that constructed an idea of China in Latin America from the nineteenth century to the present"-- Provided by publisher.
Keywords: Latin American literature -- Chinese influences.; Latin American literature -- History and criticism.; Chinese literature -- Influence.; Orientalism -- Latin America.; Modernism (Literature) -- Latin America.; China -- In literature.; Latin America -- Intellectual life.; Littérature latino-américaine -- Influence chinoise.; Littérature latino-américaine -- Histoire et critique.; Littérature chinoise -- Influence.; Orientalisme -- Amérique latine.; Modernisme (Littérature) -- Amérique latine.; Amérique latine -- Vie intellectuelle.; Chinese literature -- Influence; Intellectual life; Latin American literature; Literature; Modernism (Literature); Orientalism; China; Latin America; LITERARY CRITICISM / General; Criticism, interpretation, etc.